(The Effect of Time Duration and The Rate of Distillation on Oil Yield and Vetiverol Content in Vetiver Root). - Achmad Moestafa; Priyo Waspodo; Syaeful Hakim (Balai Besar Industri Agro, 1991)
Vetiver oil is one of the essential oils which are use as perfumeand fragrance material.It has a pleasant odour and a typical charateristic as a fixative agent in perfumes.An oil which has high vetiverol content is usually more appreciated and highly valued.An attempt to perform and high vetivero content from vetiver root by manipulating the time and rate of distillation has been carried out.It was observed that the longer the distillation was proceeded a higher yield of oil and vetiverol content was discovered.Rate of distillation seemed to have he same effect,the faster distillation was taken place, more oil and higher vetiverol was found.